The Relationship Between the Presence of Allodynia and Pain Acceptance and Somatosensory Amplification in Patients with Migraine - Aysu Yakin Olgun; Buse Rahime Hasirci Bayir; Ruziye Erol Yildiz; Sencan Sertcelik (Haseki Tıp Bülteni, 2023)

(untitled)
Aim:Allodynia is a pain disorder that adversely affects the prognosis of migraine and reduces the quality of life of patients with migraine. Thus, the study evaluated the relationship between the presence of allodynia and psychiatric aspects such as somatosensory amplification and pain acceptance in patients with migraine.Methods:The participants diagnosed with migraine who applied to the neurology outpatient clinic between October and December 2020 were included in this observational study. Structured Clinical Interview for DSM-V, Migraine Disability Assessment Questionnaire, Visual Analogue Scale, Allodynia Symptom Checklist-12, Beck Anxiety Inventory, Beck Depression Inventory, Somatosensory Amplification Scale, Chronic Pain Acceptance Questionnaire, and Acceptance and Action Questionnaire-II were applied to the patients.Results:Eighty-one patients aged 18-65 years were included. Allodynia was found in 50 patients (62%). There was mild allodynia in 18 patients, moderate allodynia in 14 patients, and severe allodynia in 18 patients. The number of analgesics used in a month was higher in patients with allodynia than without allodynia (p=0.038). Somatosensory Amplification Scale scores were found to be higher in migraine patients with severe allodynia than in mild allodynia (p=0.029).Conclusion:The presence of allodynia causes a more analgesic use in patients. Patients with severe allodynia are more aware of bodily sensations than mild severity. Allodynia does not make a difference in the levels of pain acceptance and willingness. This study will contribute to other studies in the context of acceptance and commitment in patients with migraine patients.